Age, cognitive load, and multimodal effects on driver response to directional warning. (April 2019) - Lundqvist, Linda-Marie; Eriksson, Lars
Abstract: Inattention can be considered a primary cause of vehicular accidents or crashes, and in-car warning signals are applied to alert the driver to take action even in automated vehicles. Because of age related decline of the older driver's abilities, in-car warning signals may need adjustment to the older driver. We therefore investigated the effects of uni-, bi- and trimodal directional warnings (i.e., light, sound, vibration) on young and older drivers' responses in a driving simulator. A young group of 15 drivers (20–25 years of age) and an older group of 16 drivers (65–79 years of age) participated. In the simulations, warning signal was presented at the left, the center, or the right in front of the participant. With a warning at the left, the center, and the right the correct response was to steer to the right, brake, and steer to the left, respectively. The main results showed the older drivers' responses were slower for each type of warning compared with the young drivers' responses. Overall, the responses were slower with an added cognitively loading task. The only multimodal type of warning inducing overall faster response than its constituent warning types was the vibration-sound, and only for the older drivers. Additionally, with the groups' responses collapsed, such a true multimodal effect on response time also showed for the center vibration-sound warning (i.e., braking response). The only multimodal warning showing clear reduction in response errors compared with its constituent warning types was the vibration-sound for the older drivers during extra cognitive load. The main conclusion is that older drivers can benefit from bimodal warning, as compared with unimodal, in terms of faster and more accurate response. The potential superiority of trimodal warning is nevertheless argued. Highlights: Multimodal presentation of in-car warnings can be advantageous. Bimodal warning makes older drivers' responses faster and more accurate. Trimodal warning seems no less advantageous for driver performance.